Etiology and age factors of gynecomastia - D. V. Akimov (ABV-press, 2014)
The influence of the age and intercurrent diseases on the formation of mammal gland pathology was analyzed in this research on the example of 156 males of different age groups. Three groups of pathologies were identified (true and false gynecomastia, also cancer). The prevalence of true gynecomastia is shown, the tendency to polyetiological factors mainly affecting the urogenital system is marked.